REPRESENTASI CITRA DESTINASI WISATA INDONESIA TIMUR DI MEDIA SOSIAL (ANALISIS MULTIMODALITAS PADA VLOG ARIEF MUHAMMAD “TRAVEL VLOG - #112 - SPOT ANTI MAINSTREAM DI RAJA AMPAT”) - Irdani Muhammad, Ruvira Arindita (Universitas Riau, 2019)
The presence of Media social and all things that are in it color the lives of the community, one of which is tourism activities. The Ministry of Tourism collaborates with Influencer Arief Muhammad to promote tourist areas in Raja Ampat through Vlogs. To find out the aims and objectives in the vlog, the researcher used a multimodality / semiotic social analysis from Kress and Leeuwen. After that, a Stuart Hall representation analysis is carried out to understand how the destination image is described in the vlog. The results of this study indicate that there is an emphasis on destination imagery carried out by Arief Muhammad through his vlog. The emphasized image concepts are namely tourist leisure, tourist infrastructure, general infrastructure, . The concept that is highlighted the most is Natural Resources.